Analyses for the Initial Implementation of the Inpatient Rehabilitation Facility Prospective Payment System - Carter, Grace M. (RAND Corporation, 2002)
In the Balanced Budget Act of 1997, Congress mandated that Health Care Financing Administration (HCFA) implement a Prospective Payment System (PPS) for inpatient rehabilitation. The Centers for Medicare and Medicaid Services (CMS, the successor agency to HCFA) issued the final rule governing such a PPS on August 7, 2001 and the system went into effect on January 1, 2002. This report details the analyses that RAND performed to support HCFA's efforts to design, develop, and implement the PPS. It describes RAND's research on new function-related groups, comorbidities, unusual cases, facility-level adjustments, outlier payments, facility-level adjustments, and assessment instruments. In addition, it presents RAND's recommendations concerning the payment system and discusses the researchers' plans for further research on the monitoring and refinement of the PPS.